2020
DOI: 10.3390/w12010306
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Commercial Aquaponics in Europe: Beyond the Hype

Abstract: In recent years, aquaponics has been receiving increased interest globally as a commercial food production technology and aquaponics start-up companies have been formed in most European countries. Between 2014 and 2018, the European-funded COST Action FA1305 “The EU Aquaponics Hub-Realising Sustainable Integrated Fish and Vegetable Production for the EU” created a strong network of researchers and entrepreneurs. However, surveys show that the aquaponic production in Europe is still very limited, and very few c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…Despite many hobbyists and researchers with aquaponics systems, in Europe, there are fewer cases of commercial success. A 2017 survey of the European sector by Turnšek et al (2020) identified 60 participants involved in commercial aquaponics. Amongst these is an often-cited example of commercial aquaponics success, Bioaqua Farm, which is a medium-sized facility based in the UK.…”
Section: Economic Barriers To the Success Of Aquaponicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite many hobbyists and researchers with aquaponics systems, in Europe, there are fewer cases of commercial success. A 2017 survey of the European sector by Turnšek et al (2020) identified 60 participants involved in commercial aquaponics. Amongst these is an often-cited example of commercial aquaponics success, Bioaqua Farm, which is a medium-sized facility based in the UK.…”
Section: Economic Barriers To the Success Of Aquaponicsmentioning
confidence: 99%
“…A survey of European commercial facilities highlights two major challenges: raising initial investment and administrative/legislative obstacles (e.g. environmental regulation) (Turnšek et al 2020).…”
Section: Economic Barriers To the Success Of Aquaponicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquaponics has been compared with aquaculture [2,7,8] and hydroponic [9][10][11][12] technologies in terms of production and profitability. Up to now, the research on aquaponics has been focused on sustainability [13][14][15], economic optimization [16][17][18], functional setup [19,20], stocking density [21,22], cultivation media [23,24], water recirculation [25,26], food safety [9,27], fish-plant pathogens [6,28] and beneficial microorganisms [29,30].…”
Section: Introductionmentioning
confidence: 99%